A novel graphene oxide-based fluorescence method for detection of urine glycosaminoglycans - Koesoglu, Ceren Bakir; Dede, Sureyya; Karakus, Emine; Erdogmus, Ali; Keskin, Bahadir; Onal, Hasan (WILEY, 2024)
Glycosaminoglycans (GAGs) serve as a biomarker for mucopolysaccharidoses disease. In this study, a novel fluorometric method was developed to measure total GAGs in urine. Graphene oxide (GO) and rhodamine B (RhB), a cationic fluorescent dye, were employed in the development of the method. RhB attaches to the GO surface via electrostatic attraction, leading to the quenching of its fluorescence upon the establishment of the RhB-GO complex. However, the presence of GAGs prompts a resurgence of intense fluorescence. The linear range of the method is between 5.00 and 70.00 mg/L. The total GAG levels of urine samples analyzed using the method agree with the results of the biochemistry analysis laboratory (65.85 and 79.18 mg/L; 73.30 +/- 1.76 and 72.21 +/- 2.21). The method is simple, accurate, and sensitive and may be used for both first-step diagnosis of the mucopolysaccharidoses and detection of individual GAGs for studies of GAG-related research and other biological applications.
Keywords: fluorescence-based sensor; graphene oxide; mucopolysaccharidosis; rhodamine B; RHODAMINE-B; SULFATED GLYCOSAMINOGLYCANS; HEPARAN-SULFATE; IN-VITRO; QUANTIFICATION; SENSOR; ELISA; REDUCTION; BIOMARKER; PROTEIN; Biochemistry & Molecular Biology; Biotechnology & Applied Microbiology